2014
DOI: 10.1016/j.nicl.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant network integrity of the inferior frontal cortex in women with anorexia nervosa

Abstract: Neuroimaging studies investigating the neural profile of anorexia nervosa (AN) have revealed a predominant imbalance between the reward and inhibition systems of the brain, which are also hallmark characteristics of the disorder. However, little is known whether these changes can also be determined independent of task condition, using resting-state functional magnetic resonance imaging, in currently ill AN patients.Therefore the aim of our study was to investigate resting-state connectivity in AN patients (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
44
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 77 publications
8
44
2
Order By: Relevance
“…26 Our results are also in line with a rather small pilot study (12 patients with anorexia ner vosa) suggesting reduced degree centrality (defined by the number of edges connecting to a node [i.e., brain voxel]) in patients with the disorder. 56 In support of our finding that the disruption of insula connectivity seems to be crucial in pa tients with anorexia nervosa, the same study also found changes in effective connectivity measures originating from the insula.…”
Section: Postoccipital_r_158supporting
confidence: 74%
“…26 Our results are also in line with a rather small pilot study (12 patients with anorexia ner vosa) suggesting reduced degree centrality (defined by the number of edges connecting to a node [i.e., brain voxel]) in patients with the disorder. 56 In support of our finding that the disruption of insula connectivity seems to be crucial in pa tients with anorexia nervosa, the same study also found changes in effective connectivity measures originating from the insula.…”
Section: Postoccipital_r_158supporting
confidence: 74%
“…These alterations in the functional connectivity of prefrontal, parietal and occipital areas were interpreted as suggestive of possible alterations in inhibitory control behavior (e.g. Cowdrey et al, 2012;Kullmann et al, 2014b), ruminative behavior (Cowdrey et al, 2012), visuospatial difficulties (Favaro et al, 2012) and dysfunction in bodyimage processing (Lavagnino et al, 2014). The results in eating disorders and the current results in obesity may suggest that alterations in the functional connectivity of prefrontal and occipital areas could be associated with abnormal eating behavior.…”
Section: Brain Regionmentioning
confidence: 52%
“…Patients with a current or past diagnosis of anorexia nervosa exhibited lower degree centrality in the inferior frontal gyrus (Kullmann et al, 2014b), lower connectivity within visual networks (Favaro et al, 2012), and higher connectivity of the inferior frontal gyrus and precuneus within the default mode network (Cowdrey et al, 2012). Patients with bulimia nervosa presented lower functional connectivity between the paracentral lobule and the occipital cortex (Lavagnino et al, 2014).…”
Section: Brain Regionmentioning
confidence: 99%
“…Instead, we found greater HSF connectivity for AN relative to BDD between R FFA and right fronto-insular regions. This could be related to aberrant insular and orbitofrontal activity (Frank et al ., 2012) and/or insular connectivity (Kullmann et al ., 2014) that previous studies have found in AN, and could reflect abnormal integration of high-detail face information in the context of general body awareness. Why this was observed for AN only in contrast to BDD is unclear.…”
Section: Discussionmentioning
confidence: 99%